Cause analysis of positive results of biological monitoring on pressure steam sterilization and research progress of intervention countermeasures (压力蒸汽灭菌生物监测阳性原因分析及干预对策研究进展) - WANG Baolian (王宝莲); YAN Meiqiong (颜美琼); ZHANG Yuhong (张育红); LU Xiaoyan (卢晓燕) (Association of Integrative Nursing, 2021)
Pressure steam sterilization is a commonly used clinical sterilization method, and its sterilization quality affects clinical medical safety. Biological monitoring is the gold standard for quality monitoring of pressure steam sterilization. At present, there are more and more positive cases of pressure steam sterilization biological monitoring reported in the literature, which brings unnecessary losses to hospitals and patients. This article analyzed potential factors of positive results of biological monitoring reported in different literatures, analyzed the causes of sterilization failures, and formulated intervention measures for the root causes, in order to provide a scientific basis for the prevention and control of hospital infections. (压力蒸汽灭菌是临床常用的灭菌方法, 其灭菌质量影响临床医疗安全。生物监测是压力蒸汽灭菌质量监测的金标准, 压力蒸汽灭菌生物监测阳性受诸多影响。本文综合文献中报道的生物监测阳性案例, 分析其灭菌失败原因, 并针对根本原因制定干预措施, 为做好医院感染防控工作提供科学依据。)